2020
DOI: 10.1111/dth.13807
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional antigen immunotherapy for the treatment of plane warts: A comparative study

Abstract: Intralesional immunotherapy by different antigens has shown promising efficacy and safety in the treatment of warts. However, the use of these antigens for the treatment of plane warts has been investigated in two studies only. To evaluate the efficacy and safety of three antigens; Measles Mumps, Rubella vaccine (MMR), Candida antigen, and purified protein derivative (PPD) in the treatment of multiple plane warts. The study included 120 patients who were randomly assigned to three groups, 40 patients in each g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 18 publications
3
15
2
Order By: Relevance
“…In the present study, no statistically significant relationship was found between the therapeutic response to intralesional PPD, Candida antigen, MMR, and combined therapy, and the different clinical variables. This was in agreement with many of the related studies that also reported absence of significant associations between the therapeutic response to the injected antigen and most of the clinical variables [ 12 , 23 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, no statistically significant relationship was found between the therapeutic response to intralesional PPD, Candida antigen, MMR, and combined therapy, and the different clinical variables. This was in agreement with many of the related studies that also reported absence of significant associations between the therapeutic response to the injected antigen and most of the clinical variables [ 12 , 23 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…[ 27 ] (63%) and Fawzy et al. [ 28 ] (62.5%), higher than that reported by Shaker et al. [ 29 ] (30% cure rate), and lower than that reported by Eldahshan et al.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Also, flu‐like symptoms were presented in 2 (5%) patients of the PPD group, 6 (15%) patients of the Candida albicans antigen group, and 3 (7.5%) patients of the MMR group. No recurrence of the warts was noticed after a 6‐month follow‐up period in the Candida albicans antigen and MMR groups, although it was recorded in 3 (7.5%) patients of those treated with PPD 22 …”
Section: Discussionmentioning
confidence: 85%
“…Studies have reported adverse local inflammatory reactions in 31% of patients when imiquimod cream was applied, 8 and blistering in 95% of patients when cantharidin 0.7% solution was applied 9 . Intralesional antigen immunotherapy is an emerging treatment, with a cure rate reaching 59.37% to 62.50%, while 13.33% of patients suffer from influenza‐like illness, and more than 50% experience hyperpigmentation, indurated nodules and scars accompanied by a recurrence rate of at least 30% 10,11 . Photodynamic therapy (PDT) has an effective rate of 57.5% 12 .…”
Section: Introductionmentioning
confidence: 99%